Walking with tuberculosis - Ticona, Eduardo (2019)
In countries with high tuberculosis endemicity, people are very close to this disease throughout their lives. This may be because a relative or friend develops the disease, or because in the course of their lives they themselves acquire the infection or illness. In the event, that the person is a doctor or a health professional their contact with tuberculosis will be greater, and even more so if they are involved in activities relating to its prevention and control. This article discusses my experiences with tuberculosis since childhood, as a medical student, doctor, researcher, health professional and university professor, where the professional navigates situations of a personal or emotional nature, knowledge limitations, diagnostic constraints, and even undertaking research on local problems and generating responses in prevention and control. It is surely, a common experience among health professionals who each day face this endemic which we increasingly know more about, yet it remains very difficult to control.